1997
DOI: 10.1159/000189525
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Proteinuria on Long-Term Transplant Survival in Kidney Transplant Recipients

Abstract: Long-term prognosis in kidney transplant recipients depends on multiple factors. To investigate whether mild proteinuria within the first 6 months following transplantation is a determinant of the long-term function and survival of kidney transplants, 357 patients transplanted between 1980 and 1990 were retrospectively examined over a period of 5 years. 25.5% of the patients developed an early proteinuria between 0.25 and 1.0 g/day over 6 or more months. This group was well matched concerning gender, age of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 12 publications
4
42
3
Order By: Relevance
“…31 In addition, observations have confirmed that kidney transplants are particularly vulnerable to the adverse effects of proteinuria. 32 In our cohort, we showed that the risk for proteinuria Ͼ0.5g/d at 1 year increased significantly in patients with a KwRw ratio Ͻ2.3 g/kg, fitting with previous observations that nephron underdosing is a major risk factor for proteinuria.…”
Section: Discussionmentioning
confidence: 97%
“…31 In addition, observations have confirmed that kidney transplants are particularly vulnerable to the adverse effects of proteinuria. 32 In our cohort, we showed that the risk for proteinuria Ͼ0.5g/d at 1 year increased significantly in patients with a KwRw ratio Ͻ2.3 g/kg, fitting with previous observations that nephron underdosing is a major risk factor for proteinuria.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of proteinuria reported in different studies on adult and pediatric populations varies considerable, from 11 to 82 % [4][5][6][7][8][9][10][11][12][13]. The main reason for this wide variation in prevalence of proteinuria is the different threshold used in these studies to define proteinuria.…”
Section: Prevalence Of Post-transplant Proteinuria and Methods For Itmentioning
confidence: 99%
“…In a pediatric study by Chua et al, 100 % of children had proteinuria at 1 week after RTx; however, it disappeared in 70 % of patients at 8-9 weeks posttransplant [16]. Such transient proteinuria does not have negative impact on long-term graft survival [6][7][8]20]. To the contrary, later onset proteinuria (>2-3 months posttransplant) or persistent proteinuria (duration >3 months) does have a negative impact on long-term graft survival (see below section Clinical consequences).…”
Section: Types Of Post-transplant Proteinuriamentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent proteinuria is strongly Neale J et al . Cardiovascular risk factors following renal transplant correlated to reduced function and graft survival [146] . In renal transplantation, the presence of proteinuria at 12 mo is associated with a twofold risk of CV death [147] .…”
Section: Proteinuriamentioning
confidence: 99%